TEKNIK PENERJEMAHAN UNSUR KOHESI GRAMATIKAL KONJUNGSI PADA NOVEL FĪ SABĪLI A'T-TĀJ - Ticha Fauziyatul Anwar, Muhammad Yunus Anis (CMES (Center of Middle Eastern Studies), 2018)
This research will elaborate deeply about the variant of conjunction in Arabic language and its techniques of translation. The investigating of translation techniques had the significant role in the process of translation. The translation problems had been found in the process of translation, especially related to the arabic conjunction. The analysis of variant techniques of translation towardsthe arabic conjunction can be investigated by the theory of gramatical equivalence between Arabic (L1) and Bahasa Indonesia (L2). This research aims to elaborate comprehensively about the variant construction of cohesive conjunction in Arabic language and its variant models of translation into Bahasa Indonesia. The second aim of this research is to investigate the techniques of translation toward the construction of cohesive conjunctions, especially in the Arabic prose Fi Sabiili At-Taaj which had been translated by Choirul Anwar into Bahasa Indonesia as "Ambisi Meraih Mahkota" published by Fajar Pustaka (2001). This research had been classified as descriptive qualitative model. The data had been classified using the random sampling method. The result of the research had been concluded that: (1) the Arabic adversative conjunctions had been translated into "tidak", "tetapi", and "bahkan" in Bahasa Indonesia. (2) the Arabic additive conjunctions had been translated into "dan", "lalu", and "maupun" in Bahasa Indonesia. (3) the Arabic temporal conjunctions had been translated into "kemudian" and "akhirnya" in Bahasa Indonesia. (4) the Arabic causal conjunctions had been translated into "sehingga" and "sampai" in Bahasa Indonesia. (5) several techniques had been implemented in the translations of Arabic novel FiiSabiili At Taaj, such as: literal, reduction, discursive creation, linguistic amplification, established equivalence, transposition, linguistic compression, and calque.